2013
DOI: 10.1183/09031936.00088212
|View full text |Cite
|
Sign up to set email alerts
|

Fine and coarse particulate air pollution in relation to respiratory health in Sweden

Abstract: Health effects have repeatedly been associated with residential levels of air pollution. However, it is difficult to disentangle effects of long-term exposure to locally generated and long-range transported pollutants, as well as to exhaust emissions and wear particles from road traffic. We aimed to investigate effects of exposure to particulate matter fractions on respiratory health in the Swedish adult population, using an integrated assessment of sources at different geographical scales.The study was based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
(28 reference statements)
1
28
0
Order By: Relevance
“…Population density may serve as a proxy measure for other exposures of interest. For example, less populous regions may have higher exposures to agricultural application of pesticides or herbicides, higher density of livestock, higher exposure to plant-based allergens (39), or differences in exposure to particulate matter (size and species) (40-43). For example, particulate matter (PM) in rural areas is more likely to be coarse (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population density may serve as a proxy measure for other exposures of interest. For example, less populous regions may have higher exposures to agricultural application of pesticides or herbicides, higher density of livestock, higher exposure to plant-based allergens (39), or differences in exposure to particulate matter (size and species) (40-43). For example, particulate matter (PM) in rural areas is more likely to be coarse (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…PM aerodynamic size between 2.5 and 10 micrometers), which typically arises from soil and road dust, whereas finer particulate matter (PM ≤2.5) is typically associated with industrial areas and areas of higher population density (40). Coarse PM has been associated with respiratory and cardiovascular disease and can induce oxidative stress and inflammation(41-43). It is unknown whether PM or other environmental exposures could explain geographical differences observed in EoE, but this is something that could be studied both in animal models and further epidemiologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the effects of multiple pollutants in the proximity of roads for respiratory health and allergic disease outcomes (Brunekreef et al, 1997;van Vliet et al, 1997;Nicolai et al, 2003;Kim J et al, 2004;Gauderman et al, 2005;Morgenstern et al, 2008;Rosenlund et al, 2009a;McConnell et al, 2010;Gehring et al, 2010;Clark et al, 2010;Gruzieva et al, 2012Gruzieva et al, , 2013Schultz et al, 2012;Willers et al, 2013), birth weight (Brauer et al, 2008), pre-eclampsia and preterm birth (Wu et al, 2011), fatal myocardial infarction (Rosenlund et al, 2006(Rosenlund et al, , 2009b, lung cancer (Nyberg et al, 2000) and mortality (Beelen et al, 2008a). However in their analyses these investigators used either a proximity to road measure or a specific pollutant(s), but never the effects of (multiple) pollutants within proximity to roads.…”
Section: Rationalementioning
confidence: 99%
“…In our study we did not find any statistically significant association between traffic induced particles and respiratory symptoms. However, a recent study associated increasing PM 10 and chest tightness or coughing in adults [41] and several other studies have found relationships between traffic-related air pollution and the development of asthma in children and COPD in adults [42]. Studies have also reported that children and the elderly are at a higher risk of developing respiratory diseases when exposed to very high particle concentration levels (PM 2.5 over 250 µg/m 3 and PM 10 over 1500 µg/m 3 ) [43, 44] and living close to streets with high traffic flows increases the risk of wheezing among schoolchildren [45].…”
Section: Discussionmentioning
confidence: 99%